Topics in functional analysis and algebra - USA-Uzbekistan Conference on Analysis and Mathematical Physics (Fullerton, CA 20-23 May 2014); Russo, Bernard; Aksoy, Asuman Guven; Ashurov, Ravshan; Ayupov, Shavkat (Providence : American Mathematical Society, 2016)
This volume contains the proceedings of the Special Session on Algebra and Functional Analysis. The theory of operator algebras is the unified theme for many papers in this volume. Out of four extensive survey papers, two cover problems related to derivation of various algebras of functions. The other two surveys are on classification of Leibniz algebras and on evolution algebras. The sixteen research articles are devoted to certain analytic topics, such as minimal projections with respect to numerical radius, functional equations and discontinuous polynomials, Fourier inversion for distributions, Schrodinger operators, convexity and dynamical systems.
* R. Abdullaev, Tracial and Arens algebras associated with finite von Neumann algebras* J. M. Almira and Z. Boros, A dichotomy property for the graphs of monomials* A. G. Aksoy and G. Lewicki, Characterization conditions and the numerical index* R. Ashurov and A. Butaev, On generalized localization of Fourier inversion for distributions* S. Ayupov and K. Kudaybergenov, Derivations, loal and 2-local derivations on algebras of measurable operators* S. Ayupov, K. Kudaybergenov, and A. M. Peralta, A survey on local and 2-local derivations on $C^*$- and von Neumann algebras* C.-H. Chu and B. Russo, Cohomology of Jordan triples via Lie algebras* G. Djabbarov, Extreme boundary of the space semi-additive functionals on the three-point set* N. Ganikhodjaev, Algebras with genetic realization and corresponding evolutionary population dynamics* R. N. Ganikhodzhaev and A. T. Pirnapasov, Quadratic homeomorhpisms of the two-dimensional simplex and their trajectories* A. A. Katz and O. Friedman, On universal representations and universal enveloping locally $C^*$-algebras for loally JB-algebras* A. Khalmukhamedov, Complex powers of the Schrodinger operator with singular potential* A. K. Khudoyberdiyev and Z. K. Shermatova, Description of solvable Leibniz algebras with four dimensional nilradical* I. S. Rakhimov, On classification problem of Loday algebras* I. M. Rikhsiboev, On the classification of left-symmetric dialgebras* J. P. Tian, Invitation to research of new mathematics from biology: Evolution algebras.
Includes bibliographical references and index.
Keywords: Topological algebras -- Congresses; Banach algebras -- Congresses; C*-algebras -- Congresses; Functional analysis -- Congresses